x(y+c)=

Simple and best practice solution for x(y+c)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(y+c)= equation:


Simplifying
x(y + c) = 0

Reorder the terms:
x(c + y) = 0
(c * x + y * x) = 0
(cx + xy) = 0

Solving
cx + xy = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-1xy' to each side of the equation.
cx + xy + -1xy = 0 + -1xy

Combine like terms: xy + -1xy = 0
cx + 0 = 0 + -1xy
cx = 0 + -1xy
Remove the zero:
cx = -1xy

Divide each side by 'x'.
c = -1y

Simplifying
c = -1y

See similar equations:

| 384=2x^2+16x+318 | | x^2+9=90 | | 4uv+3(uv*uv)-5uv+4(uv*uv)= | | 11x-20=101 | | 20x^3+3x^2-2x=0 | | 2x^2=62 | | 3x^2-19xy-14y^2= | | 4(x*x)+5x-8x+3(x*x)+6x-4= | | 12.15=ev | | 8(x+4)=0 | | 12.16=ev | | 12z^2-35z+25=0 | | 2x+x=11 | | 2x-1=90 | | b^2+5b+4=0 | | 8(x+4)= | | N^2+n=30 | | 8(x+28)=8 | | 1/4(3x+1)=2(2x-4)-8 | | 8x^2-5=11 | | 3(2-c)-12=-3c | | 0.3x-0.2(3-5x)=-0.5(x-6) | | -18-2x=2-8x | | x+3x+2=14 | | c=10n+26 | | r+16=15r-10 | | 10n+26=54 | | n^2-16n+36= | | w^2-26=0 | | 6y-1-4y=17 | | x/4+2=7 | | -69-2(7)(-7)= |

Equations solver categories